Anthelminthic and antimicrobial effects of hedge woundwort (Stachys sylvatica L.) growing in Southern Kazakhstan - Mukhamedsadykova, Aigerim Z.; Kasela, Martyna; Kozhanova, Kaldanay K.; Sakipova, Zuriyadda B.; Kukuła-Koch, Wirginia; Józefczyk, Aleksandra; Świątek, Łukasz; Rajtar, Barbara; Iwan, Magdalena; Kołodziej, Przemysław; Ludwiczuk, Agnieszka; Kadyrbayeva, Gulnara M.; et al. (Frontiers in Pharmacology, 2024)
The Stachys L. genus has been widely used in traditional medicine in many countries throughout the world. The study aimed to investigate the chemical composition and bioactivity of the hydroethanolic extract (50% v/v) obtained by ultrasonication from the aerial flowering parts of Stachys sylvatica L. (SSE) collected in Almaty region (Southern Kazakhstan). According to RP-HPLC/PDA analysis the leading components metabolites of the SSE belonged to polyphenols: such as chlorogenic acid and its isomers (2.34 mg/g dry extract) and luteolin derivatives (1.49 mg/g dry extract), while HPLC-ESI-QTOF-MS/MS-based qualitative fingerprinting revealed the presence of 17 compoundsmetabolites, mainly chlorogenic acid and its isomers, flavonoid glycosides, and verbascoside and with its derivatives. GC-MS analysis of the volatile metabolitess showed mainly the presence of diterpenoids and fatty acid esters. A reduction in the viability of nematodes Rhabditis sp. was obtained for the SSE concentration of 3.3 mg/mL, while 11.1 mg/mL showed activity comparable to albendazoleA statistically significant reduction in nematodes Rhabditis sp. viability was obtained for the SSE concentration of 3.3 mg/mL, while 11.1 mg/mL showed activity comparable to albendazole. The SSE exhibited higher activity against Gram-positive (MIC = 0.5-2 mg/mL) than Gram-negative bacteria and yeast (MIC = 8 mg/mL), exerting bactericidal and fungicidal effects but with no sporicidal activity. The SSE showed some antiviral activity against HCoV-229E replicating in MRC-5 and good protection against the cytopathic effect induced by HHV-1 in VERO. The SSE was moderately cytotoxic towards human cervical adenocarcinoma (H1HeLa) cells (CC50 of 0.127 mg/mL after 72 h). This study provides novel information on the SSE extract composition and its biological activity, especially in the context of the SSE as a promising candidate for further antiparasitic studies.